PROCESSES AND CIRCUMTANCES IN SHORT STORIES OF GOOD HOUSEKEEPING - JULI RACHMADANI HASIBUAN (BAHAS, 2012)
The study deals with the Analysis of Processes and Circumstances in short stories of Good Housekeeping Magazine. The data were collected from publications monthly magazine, Good Housekeeping Magazine, in its edition of January 2003, May 2003, August 2003, and December 2003. There are four Short stories used as the sample. The texts of short stories were analyzed and classified with reference to the types of Processes and Circumstances according to the Systemic Functional Grammar theories. This Study used descriptive method. The Findings indicate that the Material Process (1283, 44.66%) is dominantly used in the short stories as the representative of Process and Circumstance of Location (771, 66.07%) is dominantly used in the short stories as the representative of Circumstances. This implies that short stories are mostly written in Material Process and Circumstance of Location because both of these aspects have high numbers of using if compared with the others.